An adaptive reservation time division multiple access control protocol for robot inter-communication. (28th July 2008) - Arai, Junpei; Koyama, Akio; Barolli, Leonard
In autonomous distributed robot systems, many robots cooperate together to carry out many difficult tasks that single robots cannot realise. But, in order to cooperate together the robots should communicate with each other. Therefore, the inter-communication among robots is a very important problem to be solved. In this paper, we propose an Adaptive Reservation-Time Division Multiple Access (AR-TDMA) medium access control protocol which can realise a real-time communication among robots in a heterogeneous environment by using a reservation mechanism. Also, by using an adaptive time slot allocation method, the protocol has a flexible behaviour and can deal with the changes of number of robots. Furthermore, the proposed protocol can reduce the packet collision probability.